Squidding Around: Class Clown Fish! - Book 2 - Sherry, Kevin; Dzioba, Wes (New York, NY : Graphix, an imprint of Scholastic, 2021)
"When a silly prank lands Squizzard in deep trouble, he comes down with a case of the barnacle blues. Instead of going to the Coral Carnival with his friends, he'll have to do the swim-possible and turn Seaweed Elementary's junk-filled basement into an activity room for after-school clubs. But there just may be hidden treasures to discover if Squizzard can stop all the funny business long enough to find them..."--
Keywords: Squids -- Comic books, strips, etc; Marine animals -- Comic books, strips, etc; Friendship -- Comic books, strips, etc; Practical jokes -- Comic books, strips, etc; Elementary schools -- Comic books, strips, etc; Conduct of life -- Comic books, strips, etc; Squids -- Fiction; Marine animals -- Fiction; Friendship -- Fiction; Practical jokes -- Fiction; Behavior -- Fiction; Comics (Graphic works); Graphic novels